2019
DOI: 10.1080/10888438.2019.1615491
|View full text |Cite
|
Sign up to set email alerts
|

Does Introducing the Letters Faster Boost the Development of Children’s Letter Knowledge, Word Reading and Spelling in the First Year of School?

Abstract: Does introducing the letters faster boost the development of children's letter knowledge, word reading and spelling in the first year of school?Effects of a faster pace of letter instruction 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
1
23
0
2
Order By: Relevance
“…However, the poor performance of our discovery-learning participants even after hours of training raises questions about whether a purely discovery-based approach would be viable, given the vast body of knowledge that must be acquired in learning to read. Furthermore, school-based research increasingly suggests that a fast pace of reading instruction yields superior outcomes later (Sunde, Furnes, & Lundetrae, 2020), possibly because reading skills provide the opportunity to gain vital text experience through independent reading (van Bergen, Vasalampi, & Torppa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the poor performance of our discovery-learning participants even after hours of training raises questions about whether a purely discovery-based approach would be viable, given the vast body of knowledge that must be acquired in learning to read. Furthermore, school-based research increasingly suggests that a fast pace of reading instruction yields superior outcomes later (Sunde, Furnes, & Lundetrae, 2020), possibly because reading skills provide the opportunity to gain vital text experience through independent reading (van Bergen, Vasalampi, & Torppa, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation, supported by the results from our previous intervention (Potier Watkins et al, 2020), is that this project minimized the importance of introducing graphemephoneme correspondences simultaneously with the focused experience of learning to read in the classroom. As stated, the goal of our phonics software was to provide children with many grapheme-phoneme correspondences early in learning, a practice supported by previous observational and intervention studies (Goigoux, 2017;Sunde et al, 2020). In fact, children that participated in the intervention were exposed to more grapheme-phoneme training than children in the control group, as shown by the end test and early 1 st grade results.…”
Section: Discussionmentioning
confidence: 89%
“…In one intervention study, classrooms that taught many grapheme-phoneme correspondences early in learning (i.e. up to two a week, compared to the frequent practice of once a week) produced greater literacy outcomes (Sunde et al, 2020). In France, an observational study of 1 st grade teaching practices and student outcomes also demonstrated improved reading ability in classes where a larger number of grapheme-phoneme correspondences are taught early in the year (Goigoux, 2017).…”
Section: Numeric Responses To Literacy Curriculummentioning
confidence: 99%
“…Students saw 24 letters from the Norwegian alphabet, in upper case, in random order, one at a time (Sunde et al, 2019). They were asked to give the sound of the letter.…”
Section: Grapheme-to-phoneme Mappingmentioning
confidence: 99%